Model Pembelajaran Remap CS (Reading Concept Map Cooperative Script) untuk Pemberdayaan Keterampilan Berpikir Kritis Siswa - Kurniawati, Zenia Lutfi; Zubaidah, Siti; Mahanal, Susriyati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Critical thinking skills is a skills that need to be empowered in the face of life in the 21st century. Critical thinking skills are skills to think reflectively and reasonable to decide what is believed. Critical thinking skills can be empowered toward learning activities. One of the learning activities that can empower critical thinking skills is Remap CS (Reading Concept Map Cooperative Script) that used in biology lesson. Remap CS learning model has a syntax that can empower critical thinking skills. The purpose of this study is to empower students’s critical thinking skills in biology matter by using Remap CS learning model. This type of research is quasi experimental with nonequivalent pretest-posttest control group design. The study was conducted in science class of X4 and X1 SMA Negeri 1 Batu. Data obtained from the critical thinking skills test results were analyzed using the description rubric developed by Zubaidah, et al. (2015). The test results analyzed with Anacova and further by using LSD. The results showed that Remap CS learning model can empower students's critical thinking skills in the subject of biology.Keywords: Critical thinking skills, Remap CS